Risk perception and Community Adaptation on the coastal slums area in facing rob flood (Case Study Pluit RW 22, North Jakarta Coastal) - Heni Marta Diana MP; Osmar Shalih; Andri N.R. Mardiah (Amcolabora, 2022)
Rob flood as one of the impacts of climate change causes disruption of community activities, especially in coastal slum areas that are prone to losing their homes. However, the community's response to moving from slums is very small, even though the area of the rob flood is predicted to increase in 2030 in line with increasing global warming. This study aims to look at the risk perception of coastal slum communities in responding to the impact of climate change. This research was conducted using phenomenological methods where data is obtained through Primary Surveys (Observations and deep interviews) and Secondary Surveys (internet and digital documentation). The results showed that people in coastal slums actually know the impact of climate change, but the ability to move from where they live is limited so they carry out adaptation strategies to increase resilience in responding to the impacts of climate change.